EFEKTIFITAS PENGGUNAAN WIRE ROPE SEBAGAI TAMBAHAN TULANGAN TARIK PADA PERKUATAN LENTUR BALOK BETON BERTULANG TAMPANG T - , ANGGUN TRI ATMAJAYANTI, Prof. Ir. Iman Satyarno, ME, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Strengthening one of the efforts in recovering or increasing the strength of degraded structure. There are various types of strengthening. They depend on the level of the problem. The application of commonly used flexural strengthening methods faces several constraints in application. The objective of this research is to identify the effectiveness of wire rope as additional tensile reinforcement in T-sectional reinforced concrete beam with flexural strengthening. The test was given to two T-sectional beams, one was unstrengthened (BK) and the other was strengthened with 2 wire ropes of ï¦ 10 mm (BP). Wire rope was set without pre-tensile force under the web and then reinforced with steel plate and dyna bolt. The remolding was carried out by using 40 mm thick mortar. The test was taken by using two points loading. Results of this research showed that ductility of BP to BK specimen decreased in 0.25 ratios. Initial stiffness of BP specimen to BK specimen increased in 1.13 ratios and the equivalent stiffness decreased in 0.56 ratios. The BP specimen capacity increased to BK specimen in 1.86 ratios. Stress occurred in wire rope for BP specimen, based on the analysis result of Response-2000 and layer method, were 60.57% and 86.18%, respectively, of the ultimate stress resulted from the test. The use of wire rope for flexural strengthening in this research showed inefectivity due to slip that caused the wire rope performance to become in-optimum.